2017
DOI: 10.1136/medethics-2017-104433
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of treatment interruption trials in HIV cure research: addressing the conundrum of risk/benefit assessment

Abstract: Though antiretroviral therapy is the standard of care for people living with HIV, its treatment limitations, burdens, stigma and costs lead to continued interest in HIV cure research. Early-phase cure trials, particularly those that include analytic treatment interruption (ATI), involve uncertain and potentially high risk, with minimal chance of clinical benefit. Some question whether such trials should be offered, given the risk/benefit imbalance, and whether those who choose to participate are acting rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
91
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 39 publications
2
91
1
Order By: Relevance
“…For example, one study performed in Thailand found that participants in HIV cure research were motivated by giving back to their community and by the potential benefits not only to themselves but also to the investigators and others with HIV. 7 Additional studies have found similar other-oriented motivations. 8 People's willingness to take risk for an HIV cure also goes beyond the clinical or health benefit, and the fact that people living with HIV are often quite healthy does not preclude the possibility that a cure would significantly improve their overall quality of life.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For example, one study performed in Thailand found that participants in HIV cure research were motivated by giving back to their community and by the potential benefits not only to themselves but also to the investigators and others with HIV. 7 Additional studies have found similar other-oriented motivations. 8 People's willingness to take risk for an HIV cure also goes beyond the clinical or health benefit, and the fact that people living with HIV are often quite healthy does not preclude the possibility that a cure would significantly improve their overall quality of life.…”
mentioning
confidence: 87%
“…But the risk‐benefit ratio could depend on what people living with HIV value about seeking a cure. For example, one study performed in Thailand found that participants in HIV cure research were motivated by giving back to their community and by the potential benefits not only to themselves but also to the investigators and others with HIV 7 . Additional studies have found similar other‐oriented motivations 8 …”
mentioning
confidence: 99%
“…Supportive BSSR also includes understanding how participants make decisions to participate in HIV cure research. With the support of biomedical HIV cure research teams, socio‐behavioural scientists are increasingly able to understand decision‐making processes of those who decide to participate (or not) in HIV cure research, rather than relying on hypothetical intentions and perceptions . Supportive BSSR may also include patient‐reported outcomes (PROs) and patient‐reported experience measures (PREMs) completed by participants to assess the effects of study participation on various critical domains, such as well‐being, symptoms, functioning, adverse events and experiences with interventions, studies and ATIs .…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that many focus group participants had a profoundly positive conception of participation in health research, including studies conferring seemingly few personal benefits from the research team's perspective. 7 For example, some of these studies involved analytic treatment interruption, that is, cessation of antiretroviral treatment in order to test the effects of a cure or remission intervention. 5 Our findings were consistent with similar research in Kenya related to participant perceptions of benefit.…”
mentioning
confidence: 99%
“…Our social science research on participant experiences in the trials, however, revealed a different story about personal benefit. 7 For example, some of these studies involved analytic treatment interruption, that is, cessation of antiretroviral treatment in order to test the effects of a cure or remission intervention. Since participants were doing well on treatment, analytic treatment interruption was identified by researchers and ethics committees as a significant medical risk.…”
mentioning
confidence: 99%